ØªØ£Ø«ÙŠØ± Ù„Ø¹Ø¨Ø© "ØªØ®Ù…ÙŠÙ† Ø§Ù„ØµÙˆØ±" Ø¹Ù„Ù‰ ØªØÙÙŠØ¸ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¹Ø§Ø´Ø± ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© "Ø¯Ø§Ø± Ø§Ù„ØÙƒÙ…Ø©" Ø¨Ø§Ù†Ø¯ÙˆÙ†Ø¬ Ø¯ÙŠÙˆÙŠÙƒ Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬ Ø¬Ø§ÙˆÙ‰ Ø§Ù„Ø´Ø±Ù‚ÙŠØ© - Ririn Dwi Cahyati; Fathur Rohman; Siti Durotun Naseha (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2021)
Games are one way to improve students academic abilities and achievements in arabic language teaching, especially in understanding mufrodat, because games in education are fun, and create a happy atmosphere or renew the spirit in education. The game "guess the picture" is one of the alternative methods for Arabic. The purpose of this study is to increase the level of Arabic language teaching related to the application of educational methods "Guess the Picture" for arabic language teaching at MA Darul Hikmah Bandung Diwek Jombang. This study uses graphic media in the form of images of messages from the source to the recipients of the message. A special message is the subject of teaching Arabic. Pour the message you want to convey on the visible bananas. The results of the research in this research is the influence of picture guessing game on memorization of mufrodat for class X MA Darul Hikmah Bandung Diwek Jombang.